2009
DOI: 10.1016/j.virol.2008.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of canine parvovirus type 2c

Abstract: The sequence of the full-length gene encoding for the main capsid protein VP2 of 58 canine parvovirus (CPV) type 2c strains, along with recent CPV-2a/2b strains, was determined and analysed in comparison with reference CPV isolates. The CPV-2c strains displayed a low genetic variability and shared amino acid changes already detected in recent CPV-2a/2b isolates, with a phylogenetic clustering accounting for their geographical distribution. Analysis of the selection pressure driving CPV evolution confirmed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
111
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(135 citation statements)
references
References 19 publications
15
111
3
Order By: Relevance
“…In accordance with Pinto et al (2012), the amino acid substitution Thr440Ala was not observed in any CPV-2c sequences, as previously described in CPV-2a and CPV-2b strains from Italy (Battilani et al 2002), India (Chinchkar et al 2006), Korea (Kang et al 2008), and in CPV-2c strains from Argentina (Calderón et al 2011) and Italy (Decaro et al 2009). The 440 position is located at an important VP2 domain, undergoing positive selection and envolved independently in different populations ).…”
Section: Discussionsupporting
confidence: 85%
“…In accordance with Pinto et al (2012), the amino acid substitution Thr440Ala was not observed in any CPV-2c sequences, as previously described in CPV-2a and CPV-2b strains from Italy (Battilani et al 2002), India (Chinchkar et al 2006), Korea (Kang et al 2008), and in CPV-2c strains from Argentina (Calderón et al 2011) and Italy (Decaro et al 2009). The 440 position is located at an important VP2 domain, undergoing positive selection and envolved independently in different populations ).…”
Section: Discussionsupporting
confidence: 85%
“…Only one CPV VP2 sequence from Lithuania (LTU31CPV2) was associated with CPV-2b VP2 sequences from France, Italy, USA and Korea (cluster 6). As it was expected and reported previously (Decaro et al 2009) all the CPV-2c VP2 sequences formed a monophyletic cluster (cluster 7). Despite the strong phylogenetic association with CPV-2a ancestor, the Lithuanian CPV VP2 sequences show more or less geographically defined evolution pattern (especially five CPV samples in the first cluster), as were identified in other regions and studies (Battilani et al 2002, Wang et al 2005, Kang et al 2008.…”
Section: Discussionsupporting
confidence: 88%
“…At present, CPV-2c is broadly distributed in Italy (16), and has also been found in Spain (8), Germany, the United Kingdom (9), the United States (13), Australia (17), and Portugal (27). Although the first reports seemed to show a low pathogenicity for CPV-2c, experimental data and field observations now indicate that a more severe clinical course with higher mortality rates is associated with CPV-2c infection (10).…”
Section: Introductionmentioning
confidence: 99%